Phenotypic Characterization of Local Chickens in Dekina - Daikwo , I.S.; Okpe, A.A.; Ocheja, J.O. (International Journal of Poultry Science, 2011)
The study was conducted to characterize Local chickens of Dekina based on some phenotypic traits. A total of two thousand four hundred and twenty (2, 420) mature scavenging local chickens were covered. The most predominant plumage colour, shank colour and comb type were brown (41.75%), yellow (40.50%) and single (51%), respectively. Mean bodyweight of mature males (1.32±0.02 kg) was significantly (p